Tolkien and Rape: Sexual Terror, Sexual Violence, and the Woman's Body in Middle-earth. Issue 2 (1st June 2021) - Miller, T. S.; Miller, Elizabeth
Abstract : J. R. R. Tolkien's representation of women in his fiction has generated a number of controversies since its original publication. This essay examines two major issues: an evasiveness in Tolkien's treatment of sexual violence against women that is not disconnected from a gendered terror that underlies several moments in his works and functions to link women's sexuality and desiring with death. Specifically, we read the author's depiction of Shelob and her appetitive, arachnoid monstrosity as at once displacing sexual violence onto the monstrous feminine and evoking a revulsion at the aging female body. We next explore the consequences of the author's depictions of women and his handling of sexual violence in close connection with his own 1939 public performance of Chaucer's Reeve's Tale, a comic narrative turning on two rapes that Tolkien nevertheless conceals in a comparable fashion to his elision of sexual violence in Middle-earth.